Respiratory hypersensitivity reaction related to ingestion of raspberry - Yuki Akamatsu; Yoshio Kawakami; Shusaku Fujita; Tomoko Kawamoto; Tomoko Miyake; Yoji Hirai; Shin Morizane (Frontiers Media S.A., 2023)
A 27‐year‐old woman developed dyspnea and wheezing within 10 min after eating a piece of raspberry walnut cake, and was successfully treated with intravenous corticosteroid and intramuscular injection of adrenaline. An open oral provocation test with raspberry demonstrated immediate respiratory hypersensitivity reaction.